The effects of early combined training on the physical development of preterm infants with different gestational ages - He, Fang; Wu, Na; Ma, Xiuwei; Liu, Xiaofang; Gao, Ming; Feng, Zhichun (Frontiers in Pediatrics, 2023)
Objective To investigate the effects of early combined training on the physical development of preterm infants of different gestational ages. Methods A total of 144 preterm infants from our hospital's neonatal intensive care unit (NICU) between 2019 and 2020 were selected as the research participants and randomly divided into an intervention group (77 cases) and a control group (67 cases). The physical development and catch-up growth satisfaction rate of preterm infants in the intervention and control groups were compared at 40 weeks, 3 months, 6 months and 12 months of corrected age. Results At 40 weeks of gestational age and corrected 3 months of gestational age, the physical growth indexes of the intervention group were higher than those of the control group, with a statistical difference (P < 0.05). At the corrected age of 12 months, the body weight and length of preterm infants in the <29 weeks intervention group were still higher than those in the control group (P < 0.05). The body weight of preterm infants in the 29–32 weeks and 32–34 weeks intervention groups was higher than in the control group (P < 0.05). There was no statistical difference between the intervention and control groups in the 34–37 weeks category (P > 0.05). The catch-up growth satisfaction rates of all the physical growth indexes in the intervention group were higher than those of the control group at the corrected 3 months for all the gestational ages (P < 0.05). While those indexes in the three >29 weeks intervention groups were higher than those in the <29 weeks intervention group at the corrected age of 12 months (P < 0.05). Conclusion Early combined training can promote the early catch-up growth of preterm infants, especially in the early gestational age groups (<34 weeks), and the catch-up growth promotion can last for 12 months. The older the gestational age, the sooner catch-up growth satisfaction will occur.